Synthetic routes to treprostinil N-acyl methylsulfonamide. Issue 5 (30th January 2020) - Picken, Christina; Laing, Peter; Shen, Lei; Clapp, Lucie H.; Brocchini, Steve
Graphical abstract: Highlights: Prostacyclin mimetics such as treprostinil are used to treat pulmonary aterial hypertension. Dose limiting toxicities of treprostinil limit its clinical benefits. A candidate prodrug of treprostinil was prepared by two synthetic routes. A trepostinil synthetic intermediate may have utility to prepare prodrug analogues. Abstract: The synthesis of the prodrug candidate, treprostinil N -acyl methylsulfonamide 5 was accomplished from treprostinil 2 utilising protecting group strategies. A more direct synthesis for the prodrug was also achieved using a treprostinil triol precursor 12 and bromoacetyl acylmethylsulfonamide 14 . The overall yield of treprostinil N -acyl sulfonamide 5 directly from the triol precursor 12 is similar to the protecting group strategies because deprotonation of the acidic proton in the bromoacetyl acylmethylsulfonamide 14 reduces electrophilicity. However, the more direct route using the treprostinil triol precursor holds greater promise as a strategy to prepare a wide range of treprostinil prodrug candidates. Treprostinil N -acyl methylsulfonamide prodrug 5 exhibited a 30-fold decrease in the potency at the human prostacyclin (IP) receptor compared to treprostinil 2 in an in vitro cyclic AMP assay.